STUDENTS' APPRECIATION OFIMPLEMENTATION OF TECHNOLOGY-BASED PAI LECTURESAT SRIWIJAYA UNIVERSITY - Nurbuana, Nurbuana; Safrina, Sri; Fitriana, Fitriana; Nurhasan, Nurhasan (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2023)
This study aims to determine the appreciation given by students to the implementation of technology-based PAI lectures, especially during the pandemic. The implementation of PAI lectures, especially at this time, cannot be separated from the utilisation of technological advances. Learning activities like this, of course, cause a lot of problems, both for educators and students. It does not rule out the possibility of complaints arising from students regarding the learning process like this. The research method used is a descriptive qualitative method, by providing a closed questionnaire with a Likert scale used for data collection. The results of this study show that the appreciation given by students to the implementation of technology-based PAI lectures is diverse; including very good, good, quite good, and less good. The response was very good for the material component of PAI lectures and the ability/competence of lecturers in delivering the material. As for the other eight components, most students stated that it was good, although there were also those who stated that it was quite good with a small number, and there was even one student who stated that it was not good for the component of how to overcome problems that arise in PAI lectures.